The Influence of The Dung of Birds Nests on The Growth of and From The Results of Lettuce on The Ground Alluvial - JOKO SUTIKNO; SITI HADIJAH; RAHMIDIYANI RAHMIDIYANI (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTThis study attempts to get a dose droppings of this source the best of growth and from the sale of lettuce on the ground alluvial.Study was conducted in the garden experiment faculty agriculture, tanjungpura university, approximately 2 months from on 9 may to 8 julli years 2018. Design used in this research was complete the random consisting of five treatment droppings of this source doses, five times test, and three plant sample.Those who should 0 g droppings of this source / polybag, 125 g droppings of this source / polybag, 250 g droppings of this source / polybag, 375 g droppings of this source / polybag, and 500 g droppings of this source / polybag. Variable observed in this research is number of leaves, the number of chlorophyll leaves, the volume of the root, fresh heavy plant and heavy dry over plants. The research results show the dung of birds nests on various doses of influential not real on the number of leaves both the first week until the fourth week the number of chlorophyll leaves and the volume of the root, but had have real impact on fresh heavy plant and heavy dry plant. The provision of the dung of birds nests on various doses of give exactly the same response on the variables of number of leaves, the number of chlorophyll and the volume of the root, while variable of the weight of a fresh and heavy dry to respond good to the potter to plant lettuce, based on the research done that has been carried out it is recommended that the use of efficient even though the several doses of the dung of birds as many as 125 g / polybag.Keywords : Alluvial, Dung of Birds Nests, Selada